Abdominal palpation haptic device for colonoscopy simulation using pneumatic control - Cheng, M.; Marinovic, Welber; Watson, M.; Ourselin, S.; Passenger, J.; De Visser, H.; Salvado, O.; Riek, S. (2012)
In this paper, we describe the development of a haptic device to be used in a simulator aiming to train the skills of gastroenterology assistants in abdominal palpation during colonoscopy, as well as to train team interaction skills for the colonoscopy team. To understand the haptic feedback forces to be simulated by the haptic device, we conducted an experiment with five participants of varying BMI. The applied forces and displacements were measured and hysteresis modeling was used to characterize the experimental data. These models were used to determine the haptic feedback forces required to simulate a BMI case in response to the real-time user interactions. The pneumatic haptic device consisted of a sphygmomanometer bladder as the haptic interface and a fuzzy controller to regulate the bladder pressure. The haptic device showed good steady state and dynamic response was adequate for simulating haptic interactions. Tracking accuracy averaged 94.2 percent within 300 ms of the reference input while the user was actively applying abdominal palpation and minor repositioning.